Gut microbiome dysbiosis is associated with lumbar degenerative spondylolisthesis in symptomatic patients - Aboushaala, Khaled; Chee, Ana V.; Adnan, Darbaz; Toro, Sheila J.; Singh, Harmanjeet; Savoia, Andrew; Dhillon, Ekamjeet S.; Yuh, Catherine; Dourdourekas, Jake; Patel, Ishani K.; Vucicevic, Rajko; Espinoza‐Orias, Alejandro A.; et al. (JOR-spine, 2024)
Background Lumbar degenerative spondylolisthesis (LDS), characterized as degeneration of the intervertebral disc and structural changes of the facet joints, is a condition with varying degrees of instability that may lead to pain, canal stenosis, and subsequent surgical intervention. However, the etiology of LDS remains inconclusive. Gut microbiome dysbiosis may stimulate systemic inflammation in various disorders. However, the role of such dysbiosis upon spine health remains under‐studied. The current study assessed the association of gut microbiome dysbiosis in symptomatic patients with or without LDS. Methods A cross‐sectional analysis within the framework of a prospective study was performed. DNA was extracted from fecal samples collected from adult symptomatic patients with (n = 21) and without LDS (n = 12). Alpha and beta diversity assessed differences in fecal microbial community between groups. Taxon‐by‐taxon analysis identified microbial features with differential relative abundance between groups. Subject demographics and imaging parameters were also assessed. Results There was no significant group differences in age, sex, race, body mass index, smoking/alcohol history, pain profiles, spinopelvic alignment, and Modic changes (p >0.05). LDS subjects had significantly higher disc degeneration severity (p = 0.018) and alpha diversity levels compared to non‐LDS subjects (p = 0.002–0.003). Significant differences in gut microbial community structure were observed between groups (p = 0.046). Subjects with LDS exhibited distinct differences at the phylum level, with a significantly higher Firmicutes to Bacteroidota ratio compared to non‐LDS (p = 0.003). Differential relative abundance analysis identified six taxa with significant differences between the two groups, with LDS demonstrating an increase in putative pro‐inflammatory bacteria (Dialister, CAG‐352) and a decrease in anti‐inflammatory bacteria (Slackia, Escherichia‐Shigella). Conclusion This study is the first to report a significant association of gut microbiome dysbiosis and LDS in symptomatic patients, noting pro‐inflammatory bacterial taxa. This work provides a foundation for future studies addressing the role of the gut microbiome in association with spine health and disease. This study is the “first” to report a significant association of gut microbiome dysbiosis and the association with lumbar degenerative spondylolisthesis in symptomatic patients, noting pro‐inflammatory bacterial taxa. This work provides a foundation for future work addressing the role of the gut microbiome in association with spine health and disease.